Formulation of ayurvedic medicines and extracts of medicinal plants as an alternative therapeutic treatment option for nephrolithiasis - Shikha Sachdeva; Jaspreet Kaur; Sanjana Mehta; Renu Saharan; Parminder Nain (World Journal of Traditional Chinese Medicine, 2023)
The incidence of nephrolithiasis, commonly known as kidney stone, is increasing worldwide with significant health and economic burden. Approximately 2 million people every year in India are affected by kidney stones. It affects all ages, genders, and races, but between the ages of 20 and 49 years, it affects most frequently in men than women. Different types of stones include calcium stones, cysteine stones, struvite or magnesium ammonium phosphate stones, uric acid stones, and drug-induced stones. This review article provides information about general pathophysiology, epidemiology, clinical presentation, and pharmacological treatment, which includes ayurvedic and herbal medicines for nephrolithiasis. Further understanding of the pathophysiological link between nephrolithiasis and systemic disorders is necessary for the development of new therapeutic options.